Apraxia of object-related action does not depend on visual feedback. (February 2018) - Sperber, Christoph; Christensen, Andrea; Ilg, Winfried; Giese, Martin A.; Karnath, Hans-Otto
Abstract: Pantomime of tool use is typically affected in neurological patients with apraxia, while at the same time these patients are able to perform the use of the actual tool with less or no errors. This discrepancy is commonly explained by differences in afferent input, in particular a lack of visual online feedback from the object in pantomime. The present study investigated the role of visual feedback in apraxia of pantomime by testing neurological patients with apraxia and healthy controls in a task requiring the pantomime of tool use as well as real tool use. Visual feedback was systematically removed at different phases of the action using shutter glasses that were controlled online based on real-time motion-capturing. Data analyses revealed more errors in pantomime than in real tool use. These differences were similar in patients as well as in controls. Removal of visual feedback did not affect apractic errors specifically; it neither increased patients' apractic errors during pantomime of tool use nor transformed the patients' normal movements with a real tool into movements with apractic errors. Our findings contradict the hypothesis that apraxia patients pathologically over-rely on visual feedback. Instead, we propose that pantomime of tool use requires cognitive processes that are not necessary for real tool use and independent of visual online feedback.